2017
DOI: 10.1016/j.molimm.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and immunotherapy: The current state of play

Abstract: Cancer cells employ a number of mechanisms to escape immunosurveillance and facilitate tumour progression. The recent explosion of interest in immunotherapy, especially immune checkpoint blockade, is a result of discoveries about the fundamental ligand-receptor interactions that occur between immune and cancer cells within the tumour microenvironment. Distinct ligands expressed by cancer cells engage with cell surface receptors on immune cells, triggering inhibitory pathways (such as PD-1/PD-L1) that render im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
167
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 126 publications
0
167
0
Order By: Relevance
“…Epigenetic drugs do not only target the epithelial cells intrinsically but can also target the cross-talk between the epithelial cells and stromal cells. It has recently been shown that epigenetic therapies can sensitise cancer cells to the host immune system and boost the effects of immunotherapies such as check-point inhibitors (reviewed in [79]). This is particularly relevant to breast cancer, where treatment with check-point inhibitors has been shown to have limited efficacy compared with other cancer types [80].…”
Section: Relevance To Breast Cancermentioning
confidence: 99%
“…Epigenetic drugs do not only target the epithelial cells intrinsically but can also target the cross-talk between the epithelial cells and stromal cells. It has recently been shown that epigenetic therapies can sensitise cancer cells to the host immune system and boost the effects of immunotherapies such as check-point inhibitors (reviewed in [79]). This is particularly relevant to breast cancer, where treatment with check-point inhibitors has been shown to have limited efficacy compared with other cancer types [80].…”
Section: Relevance To Breast Cancermentioning
confidence: 99%
“…In melanoma, one clinical trial is currently investigating the combination of the BRAF/MEK inhibitors vemurafenib and cobimetinib with the DNA hypomethylating agent decitabine (NCT01876641). However, the main focus in the field appears to be the combination of epigenetic drugs, especially DNA methyltransferase and histone deacetylase inhibitors with immunotherapy, which is currently tested in numerous clinical trials [107] and the outcome of these promising approaches is highly anticipated.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, IDO1 inhibitors improved their efficacy when administered in combination with radiopharmaceutical drugs, cytotoxic anticancer agents, and so forth . Recent evidence showed that HDACi could be able to reverse immune suppression inducing an improvement in tumor recognition . Fang et al reported the first dual HDAC/IDO1 inhibitors, designed by insertion of the benzamide anti‐HDAC moiety of entinostat 9 or mocetinostat 10 into the structure of epacadostat 74 , through replacement in its molecule of the aminoethyl‐sulfamide function, exposed to the solvent in the binding with the enzyme .…”
Section: The Mtdl Approachmentioning
confidence: 99%